Correlation between academic self-efficacy and burnout originating from distance learning among nursing students in Indonesia during the coronavirus disease 2019 pandemic - Ngatoiatu Rohmani; Rosi Andriani (Journal of Educational Evaluation for Health Professions, 2021)
Purpose Distance learning, which became widespread in response to the coronavirus disease 2019 (COVID-19) pandemic, has been a burdensome challenge for students and lecturers. This study investigated the relationship between academic self-efficacy and burnout in first-year nursing students who participated in distance learning during the COVID-19 pandemic. Methods The study included 69 first-year nursing students at Jenderal Achmad Yani University in Yogyakarta, Indonesia. Data were collected in September 2020 through self-efficacy and burnout questionnaires that were distributed via email and social media for 2 weeks. The responses were analyzed using the gamma test. Results Most respondents were women (78.3%), with an average age of 19 years. Most nursing students had a moderate level of academic self-efficacy (72.5%), while only 13.0% of respondents had a low level of academic self-efficacy. However, 46.4% of students experienced severe burnout during distance learning. Cross-tabulation showed that students with moderate self-efficacy were more likely to experience severe burnout (24 respondents) (P<0.01 and r=-0.884). Exhaustion was the burnout dimension most closely associated with academic self-efficacy. Conclusion Students perceived distance learning as burdensome and reported high levels of exhaustion, which may negatively impact their academic achievement. Interventions to improve academic self-efficacy may foster students’ confidence, potentially leading to reduced burnout levels. Nurse educators should reflect upon innovative learning strategies to create a favorable learning environment for nursing students.